(untitled) - Cortada, Esther Pruna; Osuna, Sílvia (Comptes Rendus. Chimie, 2025)
The impact of distal mutations on enzyme design is analogous to the allosteric regulation effect observed in effector binding or substrate transport within heterocomplexes. Building on this analogy, we employed molecular dynamics simulations to estimate the conformational landscape of enzymes and developed the Shortest Path Map (SPM) tool. This tool identifies key conformationally relevant positions that regulate enzymatic function. In this review, we highlight various applications of the SPM method in its use as a tool for investigating the effects of distal mutations on the conformational landscape, characterizing allosteric regulation, and rationally designing enzymes. A brief description of the method is provided together with several examples reported over the years (from us and other labs) in which the SPM method has been successfully applied.